Further studies of fully developed flow through ducts of arbitrary section by the contour line-conformal mapping technique - J. Mazumdar; D. Hopkins (International Journal of Mathematics and Mathematical Sciences)
The paper discusses fully developed flow of viscous fluid through ducts of arbitrary cross-section. The method uses a constant velocity contour line in a typical cross-section of the duch as an independent variable. The amplitude of the oscillatory velocity is then obtained from an ordinary integro-differential equation. Several examples of a practical nature are given, with some that have not yet been discussed in the literature. All details are explained by graphs.